30 Ambulances attending diabetes-related emergencies in care homes – cross sectional database study. (26th April 2019) - Siriwardena, AN; Law, G; Smith, MD; Iqbal, M; Phung, V; Spaight, A; Brewster, A; Mountain, P; Spurr, K; Ray, M; Idris, I; Khunti, K
Abstract : Background: Diabetes, affecting 1 in 5 care home residents, may lead to ambulance call-outs and hospitalisation. We aimed to investigate the epidemiology of diabetes-related emergencies involving ambulance attendances to care home residents. Method: Cross-sectional design investigating ambulance attendance to people presenting with diabetes-related emergencies in the East Midlands, UK, between 2012 and 2017. We analysed dispatch and ambulance clinical data with care home data, including call category, timing, location, care home type, clinical or physiological measures, treatments, conveyance (transport to hospital) and costs. Results: Overall 2 19 722 (6.7% of 3.3 million) ambulances attended care homes over 6 years, with 12 080 (5.5%) to diabetes-related emergencies. Of 3152 care home patients categorised as having a 'diabetic problem', 1957 (62.1%) were conveyed to hospital, similar to that for community residents taking into account other factors. Factors associated with conveyance included reduced consciousness (OR 0.91, 95% CI 0.87–0.95), elevated heart (1.01, 1.01–1.02) or respiratory rate (1.08, 1.06–1.10), no treatment for hypoglycaemia (0.54, 0.34–0.86) or additional medical (but not psychiatric) problems. Ambulance costs were significantly lower when a patient was conveyed, by some £18 (95% CI £11.94–£24.12), but this would be outweighed by downstream hospital care costs. For a simulation in which all trusts' mean NHS Reference Costs were used, conveyance was no longer significant in the cost model. Conclusion: Conveyance following diabetes-related emergencies was as common for care home as for other community residents despite access to trained staff, and more likely with impaired consciousness, abnormal physiological measures or lack of treatment for hypoglycaemia. Conflict of interest: None. Funding: National institute for Health Research Collaboration for Leadership in Applied Health Research and Care East Midlands, UK.